The mediating role of cultural intelligence and cognitive flexibility in the relation between effective counsellor characteristics and multicultural counselling competencies of counsellors in Turkey - Genc, Arzu Buyruk; Sahin, Fulya Yuksel (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Our aim was to examine the mediating role of cultural intelligence and cognitive flexibility in the relation between effective counsellor characteristics and multicultural counselling competencies of counsellors in Turkey. A total of 521 counsellors participated in the study. TThe Effective Counsellor Characteristics Assessment Scale, Multicultural Counselling Competencies Scale, Cultural Intelligence Scale, and Cognitive Flexibility Inventory were used to collect the data. Cognitive flexibility and cultural intelligence were found to play a full mediating role between effective counsellor characteristics and multicultural counselling competencies.
Keywords: Multicultural counselling competencies; effective counsellor characteristics; cognitive flexibility; cultural intelligence; RELIABILITY; MODEL; Psychology